Acute irritation of tetracyclic c-4-hydroxyphenylcalics [4] pyrogalolarene on skin of albino rabbits - Aditya Nugraha; Dwi Aris Agung Nugrahaningsih; Rul Afiyah Syarif; Mia Munawaroh Yuniyanti; Ikhsan Nur Salim; Ratna Sari; Jumina; Eti Nurwening Sholikhah (Indonesian Journal of Pharmacology and Therapy, 2020)
C-4-hydroxyphenylcalix[4] pyrogalolarene (Pg4OH) is a synthetic chemical compound that shows strong antioxidant activity. It is potential to be developed as UV skin protector. For topical admission, an acute skin irritation test is being prerequisite to be fulfill. This study was conducted to investigate the irritation effect of Pg4OH on the skin. In vivo study by quasi experiment with posttest only design was carried out by employing 3 adult male albino rabbits. The back hair was shaved at 24 h before the treatment. The Pg4OH was smeared on the bare shaved-skin and left naturally within 4 h. The observation began at 24, 48 and 72 h after exposure. The erythema and edema scores were measured. Calculation by using primary irritation index (PII) was applied. Calculation was categorized with globally harmonized system (GHS) and international organization for standardization (ISO) parameters. As a result, among three rabbits, only one animal shown erythema and edema with very small size (score: 1), on 3 sites, at 72 h. Both the control site and the sample sites gained same score. Two other rabbits were obtained 0 value at each observation location. According to the PII, the observed data was obtained score 0.0093 (very light or negligible). It can be concluded that the tetracyclic compound of Pg4OH does not irritate the skin.